Briefing note: Building on farmers' perception and traditional knowledge: biodiversity management for climate change adaptation strategies - Bioversity International; Asociación para la Naturaleza y el Desarrollo Sostenible; Community Technology Development Trust; Southeast Asia Regional Initiatives for Community Empowerment; Oxfam Novib (2013)
The factsheet presents some initial findings of a multi-country climate change survey carried out in Peru, Zimbabwe and Vietnam in 2012-2013 by the Asociación para la Naturaleza y el Desarrollo Sostenible (ANDES), Community Technology Development Trust (CTDT), the Southeast Asia Regional Initiatives for Community Empowerment (SEARICE) and Oxfam-Novib to assess perceptions of indigenous peoples and smallholder farmers on climate change. Study confirms that these actors are adapting to climate change and they do so by extending their traditional knowledge of weather predictions, biodiversity management and cropping calendars. The study highlights farmers’ seed systems as an important aspect of adaptation. It recommends the strengthening of social networks, including through biodiversity fairs, to support farmers’ exchange of seeds and knowledge, particularly amongst women. Indigenous peoples and smallholder farmers are critical actors in the collective global responses to challenges posed on food security and nutrition in the context of climate change and more efforts are needed to support their work.